Accelerated Immunodeficiency-associated Vaccine-derived Poliovirus Serotype 3 Sequence Evolution Rate in an 11-week-old Boy With X-linked Agammaglobulinemia and Perinatal Human Immunodeficiency Virus Exposure. (14th May 2019) - Jallow, Sabelle; Wilmshurst, Jo M; Howard, Wayne; Copelyn, Julie; Seakamela, Lerato; Chan, Koon-Wing; Sebunya, Robert; Sibiya, Rosinah; Du Plessis, Heleen; Jacobs, Charlene; Berkowitz, Natacha; Blumberg, Lucille; et al.
Abstract: Primary B-cell immunodeficiencies are risk factors for the generation of vaccine-derived polioviruses. We report immunodeficiency-associated vaccine-derived poliovirus serotype 3 in an 11-week-old boy with X-linked agammaglobulinemia. Unique characteristics of this case include early age of presentation, high viral evolutionary rate, and the child's perinatal exposure to human immunodeficiency virus.